The Outcome of Limberg Flap Procedure in the Management of Primary Chronic Sacrococcygeal Pilonidal Sinus Disease - Bashar Akram Al-Bayati; Salah Salih Mohammed; Mohamad Theyab Hamad (Indian Journal of Forensic Medicine & Toxicology, 2022)
Introduction: Sacrococcygeal pilonidal sinus (PNS) is a common chronic benign disease of young agegroup, associated with morbidity, often with a prolong loss of normal activity. Still there is ongoingdebate regarding the best treatment option as all the methods have complications, although; the currentevidence supports the use of off- midline techniques because of lower recurrence rates and avoidanceof all disadvantages of open treatment.This study was done to determine the postoperative outcomeof rhomboid excision and Limberg flap reconstruction as a main procedure in the treatment of PNSdisease in our institute.Patients and Method: A prospective study conducted at the Department of General Surgery- BaqubaTeaching Hospital- Diyala- Iraq, from January 2017 to June 2019, in which 98 patients (78 male and20 female) with chronic primary sacrococcygeal PNS were enrolled. The age of the patients rangedbetween 16 – 38 years. Patients with acute abscess were first treated by incision and drainage beforedefinite surgery. Patients were operated by rhomboid excision and Limberg flap reconstruction.Results: In this study, 98 patients were enrolled, 78 male (79.59 %) and 20 female (20.4%) with maleto female ratio of 3.9:1. The age of the patients ranged between 16 to 38 years with the mean age of25 years. During the follow up period; 6 patients (6.12%) developed seroma, 4 patients (4.08%) hadinfection and 4 patients (4.08%) had recurrent sinus after few months and one patient (1.02%) hadwound disruption.Conclusion: Rhomboid excision and Limberg flap reconstruction of PNS diseaseis safe and reliabletechnique with low complication and recurrence rates if performed according to appropriate surgicalprinciples.